2022
DOI: 10.3390/app12073239
|View full text |Cite
|
Sign up to set email alerts
|

Educational AI Chatbots for Content and Language Integrated Learning

Abstract: Using advanced artificial intelligence (AI) technology in learning environments is one of the latest challenges for educators and education policymakers. Conversational AI brings new possibilities for alternative and innovative Information and Communication Technologies (ICT) tools, such as ΑΙ chatbots. This paper reports on field experiments with an AI chatbot and provides insights into its contribution to Content and Language Integrated Learning (CLIL). More specifically, this paper presents an experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 22 publications
3
58
0
10
Order By: Relevance
“…(2013) Massively multiuser online learning (MMOL) To propose the construction of a learner role-play to enhance the foreign language abilities of learners 35 international students at the University of Alcalá Such a setting encourages an immersive, creative, and collaborative foreign language learning experience Lubold et al. (2021) Social robot, Quinn To investigate how social conversation and entrainment influence self-reported and behavioral rapport responses 48 college students A social, trainable robot is capable of producing self-reported and linguistic responses that are nuanced and based on individual variations Luo and Cheng (2020) A collaborative multimedia teaching ​model To investigate the use of artificial intelligence technologies in individual foreign language learning N/A An interactive platform for teaching foreign languages Mageira et al. (2022) AsasaraBot is introduced to the students as the Goddess of Snakes To teach cultural information to high school pupils in a foreign language 61 Greek students who study both English and French AI chatbot technology for interactive ICT-based learning is appropriate for the study of foreign languages and cultural material Mazur et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2013) Massively multiuser online learning (MMOL) To propose the construction of a learner role-play to enhance the foreign language abilities of learners 35 international students at the University of Alcalá Such a setting encourages an immersive, creative, and collaborative foreign language learning experience Lubold et al. (2021) Social robot, Quinn To investigate how social conversation and entrainment influence self-reported and behavioral rapport responses 48 college students A social, trainable robot is capable of producing self-reported and linguistic responses that are nuanced and based on individual variations Luo and Cheng (2020) A collaborative multimedia teaching ​model To investigate the use of artificial intelligence technologies in individual foreign language learning N/A An interactive platform for teaching foreign languages Mageira et al. (2022) AsasaraBot is introduced to the students as the Goddess of Snakes To teach cultural information to high school pupils in a foreign language 61 Greek students who study both English and French AI chatbot technology for interactive ICT-based learning is appropriate for the study of foreign languages and cultural material Mazur et al.…”
Section: Resultsmentioning
confidence: 99%
“… Luo and Cheng (2020) examined the use of an L2 chatbot in foreign language learning where the authors found that individual L2 learners with various cultural heritages, thinking patterns and growth backgrounds respond differently to the same linguistic form. Mageira et al. (2022) presented a report on field experiments with an L2 chatbot, AsasaraBot, and their findings showed that the majority of the participants has a positive attitude towards AsasaraBot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical Arabic [73], [60], [72] Education English [117], [86], [90], [108], [118],[1 07], [45], [112], [109], [122] Classical and MSA Arabic [50], [51] MSA Arabic [54], [58], [57], [55], [52], [53], [ 67], [66], [110], [63], [65] Arabic dialects: Saudi Arabic dialect and Jordanian [77], [78] Healthcare English [41], [44], [47], [70], [49], [71], [ 119] MSA Arabic [74], [111] Arabic Dialects: Egyptian [100] Tourism and airline English [35], [43] MSA Arabic [59], [75], [46], [113], [115] Business and customer service English [87], [69], [121],…”
Section: Religionmentioning
confidence: 99%
“…This change has been accompanied with a shift from teacher-centered to learner-centered approaches to learning, as learners become involuntarily dependent on technology (Dhawan, 2020) as part of the new normal (Zhou et al, 2022). Previous research looked into how learners accepted diverse forms of technologies including social networking tools (Alvi, 2021a) such as WhatsApp (Kaur et al, 2021), learning management systems (Camilleri & Camilleri, 2021), artificial intelligence for integrated learning (Mageira et al, 2022), and feedback (Alvi, 2021b). Based on these studies, learners' perceptions and acceptances emerged as central factors in shaping their learning experience (LE), in a technology-supported learning environment (Huang & Liaw, 2018).…”
Section: Recommendations and Conclusionmentioning
confidence: 99%